STUDY ON FIRE PROCESS KINETICS OF PARTICLEBOARD - Van Chu, Tran (Journal of Forestry Science and Technology, 2016)
Fire-retardant particleboard has been studied in Vietnam recently. There are many factors affecting the quality of fire-retardant particleboard, in which the factors of fire process kinetics are very important. Fire process kinetics is expressed through multiple criteria, such as thermal conductivity, mass loss rate of the samples, temperature change in the samples, time to spread fire, time to flame, smoldering time of particleboard, etc. The purpose of this research is to study the kinetics of fire process of particleboard produced from Styrax tonkinensis wood and 3 fire-retardant mixture formulas, then select a fire retardant mixture formula suitable to technology and production conditions in Vietnam. The study results showed: 1) The 3 fire retardant formulas enable to produce fire-retardant particleboard which meet the basic requirements of particleboard used in construction and furniture. The requirements include: good fire resistance, less effect on board strength, etc. Among these 3 fire-retardant mixture formulas, the third one is most suitable to the current production conditions in Vietnam; 2) During the studying on kinetic factors of fire process, we can propose the solutions to prevent and fight fires and thereby giving the technology suitable with specific technology and production conditions; 3) Production technology of fire-retardant particleboard, according to the research results, can be applied entirely on practice production with the equipment used in the common particleboard production nowadays.